Study Of P450 Enzyme Activity In Liza aurata In The ALKabeer AL Shamaly River Estuary Area (Latakia University Journal -Biological Sciences Series, 2021)
In this study, we showed  that the activity of Cyt-P450 in Liza aurata fish collected from the estuary of the river of Al Kabeer Al Shamaly area, ranges between 2-5 km2. It is considered as one of the methods studying organic pollutants. the biomarkers act as early warning signals on the resulting toxic risks as a reaction to the entry of pollutants into the body.The activity of Cyt-P450 has been studied for male and female of Liza aurata. The result showed that the activity ranged between 2.132 - 29.905 nmol/min/nmol P450 for the males and 2.450, 3.373 and 32.296 nmol / min / nmol p450 for the females.Our research took into consideration some of the environmental factors such as temperature, salinity and conductivity, which showed their direct effects on the activity of Cyt-P450, especially during fertilization periods.